Multinationals and Unionism in Indonesia - Rachmawati, Riani; Ruyter, Alex de (UI Scholars Hub, 2007)
This paper presents a critical analysis of the factors shaping the interaction between multinationals and trade unions in Indonesia, focusing on the recent period of democratization following the downfall of the Suharto regime. It has been suggested that union growth risks undermining Indonesia’s competitive advantages (cheap labour) and could encourage the exit of multinationals to cheaper competitors. In order to test this proposition, two case studies were conducted: one in the automotive industry and the other in the banking industry. The paper first provides an overview of multinational activity and FDI in Indonesia, and their interaction with a nascent union movement. This is followed by presenting the findings of interviews conducted at the multinational enterprises with managers and union officials; to provide empirical insights into the bargaining process. The final part of the paper provides a preliminary assessment of the impact of union behaviour on MNC profitability and competitiveness in Indonesia. In contrast to traditional views of unions as impeding MNC profitability and “encouraging” exit, the paper finds that unions and MNCs can engage in constructive partnerships, but that pressures and contradictions in the relationship remain.